Ocular Lesions in Congenital Toxoplasmosis in Santa Isabel do Ivaí, Paraná, Brazil. Issue 9 (September 2017) - Sanders, Ana Paula; dos Santos, Tatiane; Felipe, Cleusa Kimie Koike; Estevão, Maria Lucia; Cícero, Caroni; Evangelista, Fernanda; Manrique, Carlos Alexandre; Mizutani, Angélica Sayuri; Falavigna-Guilherme, Ana Lucia
Abstract : We verified clinical and psychopedagogic aspects of congenital cases with ocular sequelae, 13 years after toxoplasmosis outbreak in Santa Isabel do Ivaí, and current seroprevalence of this zoonosis in pregnant women. Audiologic and ophthalmologic evaluations were performed in congenital cases, in addition to collection of clinical and psychopedagogic data. In pregnant women, current seroprevalence was observed. Among affected teenagers, 2 of 5 are behind in school grade, and 4 of 5 reported learning difficulties, requiring psychopedagogic monitoring, as well as ocular complaints. We observed predominance of small, scarred, dispersed, type II chorioretinal lesions (hypopigmented halo and hyperpigmented central area), and 1 case of ocular relapse. All patients presented normal audiologic assessment. Among 131 pregnant women, 62 (47.3%) were seronegative and 39 (29.8%) were IgG reactive. Only 1 reported acquiring infection during the outbreak. This is one of the few studies in Brazil showing the outcome of congenital toxoplasmosis, a decade after infection, in one of the world's largest outbreaks. Abstract : Supplemental Digital Content is available in the text.